Concept Mapping as a Method to Engage Patients in Clinical Quality Improvement - LaNoue, Marianna (Ann Fam Med, 2016)
Patient engagement has become a primary care research and practice priority. Little guidance exists, however, on how best to engage patients in primary care practice improvement, or how to measure the impact of their engagement. We present an overview of group concept mapping as a method for engaging patients in primary care practice improvement. We detail the group concept mapping process as a tool for use in primary care practice improvement, research, and evaluation, and we present resources to enable researchers and practice leaders to use this tool in practice improvement. To illustrate the method, we present a practice-based quality improvement project conducted with patients and staff at a large urban academic primary care practice.